Expressão dos fatores de virulência em Candida albicans: confiabilidade dos métodos microbiológicos e efeito do tratamento fotodinâmico - Arantes, Paula Tamião [UNESP] (2015)
This study aimed to: I. to establish a reproducible protocol using the agar-Based methodology to evaluate the production of the phospholipase and proteinase by the species Candida albicans (C. albicans); II. to analyze the expression of virulence factors after photodynamic inactivation (PDI) mediated by curcumin (CUR). In the first study 30 clinical isolates and a reference strain of the C. albicans were used to obtain cell suspensions (108CFU/mL) that were plated in specific media. Three independent variables (number of replicates, background color and reading instrument) originated eight reading protocols. The intra- and inter-examiner reproducibilityof the enzyme production measure (Pz) was assessed using the intraclass correlation coefficient (ICC). The enzyme proteinase presented two protocols with good intra-rater reproducibility (ICC≥0.71) and the readings in triplicate against natural light showed the highest inter-examiner reproducibility for Pz-proteinase values. Three protocols with 'Good' intra-rater agreement for Pz-phospholipase were selected for interexaminer analysis. Caliper and computer readings, performed in triplicate, showed 'Very Good' reproducibility. In Study II, CUR at 0,1μM was used with LED light to promote sublethal dose of the PDI. The treatment group (C+L+) had its cells photosensitized with CUR and illuminated. The control group consisted of the samples that received only CUR (C+L-), and another which received neither CUR or light (C-L-). The adhesion ability was evaluated by means of CFU/mL and the XTT method. Biofilm formation was analyzed by means of CFU/mL, XTT and Crystal Violet (CV). The ability to secrete degradative enzymes was evaluated by the agarbased method and a colorimetric method. The results CFU/mL, XTT, CV were evaluated using a one-way multivariate analysis of the variance (MANOVA) and when statistically significant effects were detected, One... (Complete abstract electronic access below)